Strategi inovasi untuk Meningkatkan Daya Saing UMKM Probolinggo di Era Digital - Dila Kumalatul; Deddy Junaedi; Eva Cahya; Siti Hariro; Yesi Syifa’iyah (New Economy, 2025)
In order to increase MSMEs' competitiveness in Probolinggo in the digital age, this study attempts to identify and develop efficient digital innovation techniques. Leveraging the use of technology like social networking, e-commerce, and business management apps in MSME operations is the main goal. Changes in customer behavior and worldwide competitiveness brought on by quick technical breakthroughs are the biggest obstacles MSMEs in Probolinggo face, necessitating innovation. To investigate the innovation tactics used, the research combines a case study methodology with a qualitative approach. The results show that in order to increase operational effectiveness and broaden their market reach, MSMEs must make use of digital technologies like social media and e-commerce platforms. Creating a distinctive brand by incorporating regional values has worked well for product differentiation. Additionally, MSMEs can create products that better suit consumer demands and market trends by using data analytics for market research. In light of the increasingly competitive digital era scenario, this study offers Probolinggo's MSMEs useful insights on how to maximize digital technologies and strategic innovations, boosting their competitiveness and broadening their market reach.